2014
DOI: 10.1007/s00213-014-3444-2
|View full text |Cite
|
Sign up to set email alerts
|

Serotoninergic effects on judgments and social learning of trustworthiness

Abstract: This is evidence that serotonin systems can mediate explicit assessment and social learning of the trustworthiness of others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…In line with previous research using a similar peer-pressure procedure 29 31 , 35 , 36 , we showed that, on average, participants tested online as well as those tested in the laboratory aligned their ratings on public information when the feedbacks it provided conflicted with the participants’ social preferences. This alignment was more pronounced for trials paired with a strong than a moderate disagreement.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with previous research using a similar peer-pressure procedure 29 31 , 35 , 36 , we showed that, on average, participants tested online as well as those tested in the laboratory aligned their ratings on public information when the feedbacks it provided conflicted with the participants’ social preferences. This alignment was more pronounced for trials paired with a strong than a moderate disagreement.…”
Section: Discussionsupporting
confidence: 91%
“…To test these hypotheses, we adapted a well-validated face evaluation task 29 31 , 35 , 36 that we administered online to 300 participants recruited via a crowdsourcing platform (Amazon Mechanical Turk). Participants were asked to rate unfamiliar faces on the trustworthiness dimension on an 8-point Likert scale before and after watching to the most frequent ratings provided by a fictive group of peers, i.e., the public information (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Citalopram tends to increase reactivity in emotion-potentiated startle paradigms (Browning et al 2007;Harmer et al 2003) and increase the labelling of facial cues as fearful (Harmer et al 2003). Recently, Simonsen et al (2014) showed that females receiving citalopram rated face stimuli less trustworthy compared to placebo. Acute citalopram administration may increase alertness towards emotionally salient environmental stimuli like neutral human faces.…”
Section: Discussionmentioning
confidence: 99%
“…by a serotonergic agent e.g. 27,28 ); this 343 possibility should be explored in future studies. 344…”
Section: Discussion 295mentioning
confidence: 99%